WATER RETENTION OPTION OF DRAINAGE SYSTEM FOR DRY SEASON CORN CULTIVATION AT TIDAL LOWLAND AREA - Bakri, Bakri; Imanudin, Momon Sodik; Bernas, S. Masreah (AGRIVITA, Journal of Agricultural Science, 2015)
Corn production obtained was 6.4 t ha-1. This condition was very promising though still below the maximum national production. The aapplications of subsurface drainage was still not optimumum due to the supply of water from the main system was not the same because of the soil physical properties diversity and topography differences.This condition implied that installation of sub-surface drainage at dry season had function as water retention, not as water discharge. There-fore, network function was inverted from water discharge into water retention. It had impact on the development of optimum water surface that flow in capillary mode to fulfill the crop’s water requirement. Farming constraint at tidal lowland area is about water management related to the nature of excessive water during wet season and insuf-ficient water during dry season. This field research objectives was to find out the corn crop culti-vation in August 2014 which entered dry season.The iinstallation of subsurface drainage that previously had functioned as water discharge was converted into water retention. The research results showed that corn had grown well during peak dry season period (October) in which water table was at –50 cm below soil surface, whereas water table depth was dropped to –70 cm below soil surface in land without subsurface drainage.